2013
DOI: 10.1161/circulationaha.112.092353
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Myocardial Infarction and Its Relationship to Angiographic Collateral Flow in Territories Supplied by Chronically Occluded Coronary Arteries

Abstract: Background-Despite complete interruption of antegrade coronary artery flow in the setting of a chronic total occlusion (CTO), clinical recognition of myocardial infarction is often challenging. Using cardiac MRI, we investigated the frequency and extent of myocardial infarction in patients with CTO, and assessed their relationship with regional systolic function and the extent of angiographic collateral flow. Methods and Results-We included 170 consecutive patients (median age, 62 years) with angiographically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
62
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 53 publications
9
62
3
3
Order By: Relevance
“…The number is expected to rise as a result of improved survival of patients with acute coronary syndrome, due to rapid advances in medical and interventional therapy for patients with coronary artery disease. Despite the complete interruption of antegrade blood flow caused by heavy atherosclerotic plaque burden or arterial thrombosis, the frequency of myocardial infarction in areas subtended by chronic total occlusion varies considerably (Fefer et al, 2012), and the degree of myocardial injury downstream of epicardial chronic total occlusion is inversely correlated with the degree of angiographic coronary collateral circulation (Choi et al, 2013). Well-developed coronary collaterals have the potential to alleviate myocardial ischemia, preserve residual contractility, reduce cardiovascular events (Regieli et al, 2009;Meier et al, 2012), and even save lives in patients with severe coronary artery occlusion (Meier, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The number is expected to rise as a result of improved survival of patients with acute coronary syndrome, due to rapid advances in medical and interventional therapy for patients with coronary artery disease. Despite the complete interruption of antegrade blood flow caused by heavy atherosclerotic plaque burden or arterial thrombosis, the frequency of myocardial infarction in areas subtended by chronic total occlusion varies considerably (Fefer et al, 2012), and the degree of myocardial injury downstream of epicardial chronic total occlusion is inversely correlated with the degree of angiographic coronary collateral circulation (Choi et al, 2013). Well-developed coronary collaterals have the potential to alleviate myocardial ischemia, preserve residual contractility, reduce cardiovascular events (Regieli et al, 2009;Meier et al, 2012), and even save lives in patients with severe coronary artery occlusion (Meier, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…3 In the context of the population of interest and compared with other clinical studies in the field, 4 the present study is well powered, the fact of which renders the mentioned figures reliable. The data shown are well anchored in existing knowledge by illustrating a direct link between infarct size and the occurrence of ECG and LV functional signs of scar.…”
Section: Prevalence Of Myocardial Scar and Collateral Flow: The Presementioning
confidence: 68%
“…The careful work by Choi et al 3 has shown convincingly that increasingly sensitive detectors of myocardial scar raise its prevalence from a mere quarter of the population with chronic occlusion as defined by ECG Q waves to 42% by the history of prior ischemic symptoms suggestive of myocardial infarction, 69% based on the presence of regional left ventricular (LV) wall-motion abnormalities as assessed by cardiac magnetic resonance imaging, and 86% as defined by myocardial late gadolinium enhancement. 3 In the context of the population of interest and compared with other clinical studies in the field, 4 the present study is well powered, the fact of which renders the mentioned figures reliable.…”
Section: Prevalence Of Myocardial Scar and Collateral Flow: The Presementioning
confidence: 99%
See 2 more Smart Citations